A gente tem que falar aquilo que a gente tem que provar: a geopolítica do risco e a produção do sofrimento social na luta dos moradores do Bairro Camargos em Belo Horizonte - MG - Raquel Oliveira Santos Teixeira (2014)
The thesis examines the conflict experienced by residents of Camargos district in Belo Horizonte when an incinerator of industrial and hospital waste was installed near their homes. The analysis begins reconstructing the trajectory of the neighborhood and its historic process of transformation into a populated and urbanized locality fulfilled with feelings of belonging. Emphasis is given to entanglements between the production of the landscape and the production of bodies which inhabit it highlighting a geopolitic of risks that reproduces class relations in the urban space. In the environmental regulation of risks, it is observed that the local resistance to incineration is captured by the requirements of a specific logic based on damage proving. In this conflict, I emphasize that the power to deal with the environmental health problems is strongly constrained by regulatory dynamics and their regimes of knowledge production, including the use of scientific uncertainties and controversies regarding incineration and its effects on health. This work also examines the processes of silencing and subordination faced by the residents who are invited to participate in the deliberative and regulatory dynamics but have their claims and narratives denied. Consequently, I argue that in the struggle for providing evidence of the damage, the institutional spaces for participation and advocacy accommodates mechanisms that produce social suffering.